Hydrodynamic Performance of a Dual-Pontoon WEC-Breakwater System: An Analysis of Wave Energy Content and Converter Efficiency - Haoyu Ding (Energies, 2024)
A dual-pontoon WEC-breakwater system is proposed to optimise space utilisation and reduce construction costs by integrating wave energy converters (WECs) with breakwaters. Previous parametric studies on the dimensions and layout of WECs have primarily used potential flow theories, often neglecting the viscous effects in wave–pontoon interactions. In this research, I employ a fully nonlinear viscous model, OpenFOAM®, to address these limitations. I examine multiple parameters, including the gap width between the pontoons, the draft, and the structure breadth, to assess their impact on the functional performance of this hybrid system. Furthermore, I discuss the accurate hydrodynamic performance of waves interacting with multiple floating structures and explore how various parameters influence the dual-pontoon WEC-breakwater integrated system’s functionality. I discuss a novel analysis of the effective frequency bandwidth, considering both wave energy conversion efficiency and wave attenuation efficiency, to reflect the overall performance of the integrated system. This paper investigates wave–structure interactions and suggests optimisation strategies for the WEC-breakwater integrated system.